2013
DOI: 10.1002/cphc.201300754
|View full text |Cite
|
Sign up to set email alerts
|

Charge Fluctuations and Ethylene‐Group‐Ordering Transition in β′′‐(BEDT‐TTF)4[(H3O)Fe(C2O4)3]⋅Y Molecular Charge‐Transfer Salts

Abstract: The polarized infrared reflectance and Raman spectra of the three quasi-two-dimensional β''-(BEDT-TTF)4[(H3O)Fe(C2O4)3]⋅Y bifunctional charge-transfer salts, where BEDT-TTF = bis(ethylenedithio)tetrathiafulvalene and Y = C6H5Br, (C6H5CN)0.17(C6H5Br)0.83, (C6H5CN)0.4(C6H5F)0.6, have been measured as a function of the temperature. Signatures of charge inhomogenity have been found in both Raman and infrared spectra of the β''-(BEDT-TTF)4[(H3O)Fe(C2O4)3]⋅Y superconductors. A 100 K transition to a mixed insulating/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
2
2
Order By: Relevance
“…Different works [46,47], studying gold nanoparticles, claimed that interband terms should have minimal or no effect on plasmon absorption with temperature since interband transition energies (typically of the order of the eV) are very high compared to vibrational energy (∼10 −2 eV). Our results, and some recent experimental works performed on different materials (ultrathin Au films [15], bis(ethylenedithio)tetrathiafulvalene [48], BSTS [49], LiInSe [14]), suggest a temperature dependence for interband terms contradicting the previous statement. Usually a parametric approach is preferred [14,48] to fit the experimental observations, performed by an ad hoc change of Lorentz-Drude parameters.…”
Section: Wavelength Nm Energy Evcontrasting
confidence: 98%
See 1 more Smart Citation
“…Different works [46,47], studying gold nanoparticles, claimed that interband terms should have minimal or no effect on plasmon absorption with temperature since interband transition energies (typically of the order of the eV) are very high compared to vibrational energy (∼10 −2 eV). Our results, and some recent experimental works performed on different materials (ultrathin Au films [15], bis(ethylenedithio)tetrathiafulvalene [48], BSTS [49], LiInSe [14]), suggest a temperature dependence for interband terms contradicting the previous statement. Usually a parametric approach is preferred [14,48] to fit the experimental observations, performed by an ad hoc change of Lorentz-Drude parameters.…”
Section: Wavelength Nm Energy Evcontrasting
confidence: 98%
“…Our results, and some recent experimental works performed on different materials (ultrathin Au films [15], bis(ethylenedithio)tetrathiafulvalene [48], BSTS [49], LiInSe [14]), suggest a temperature dependence for interband terms contradicting the previous statement. Usually a parametric approach is preferred [14,48] to fit the experimental observations, performed by an ad hoc change of Lorentz-Drude parameters. However, we preferred to reduce the number of free parameters, keeping the TD for Drude parameters.…”
Section: Wavelength Nm Energy Evcontrasting
confidence: 98%
“…These salts belong to the monoclinic group of the family with a β"-packing type of radical cation layers. The conducting and structural properties of β"-crystals strongly depend on the size, shape, and chemical nature of the guest solvent molecule G. In some crystals with G = halobenzenes and M = Fe, the structural phase transition from the monoclinic to the triclinic state was found upon lowering the temperature [21,22,36]. In our recent work we showed that the same transition also exists in superconducting Fe crystals with G = 2-ClPy and 2-BrPy (T c = 4.0 K and 4.3 K, respectively) [25].…”
Section: Discussionmentioning
confidence: 99%
“…The structural phase transitions in several superconducting crystals (G = PhBr and PhCl/PhCN or PhF/PhCN mixtures) are accompanied by subtle changes in the ordering of the ethylene groups of BEDT-TTF, the consequences of which are phase transitions of these crystals from metallic to mixed metallic/insulating states. [19] According to the theoretical considerations of Merino and McKenzie, [21] the existence of this state precedes the appearance of superconductivity in crystals of organic conductors with a quarter-filled conduction band. To get additional information about the family of crystals containing halogenated solvents, we first used different monohalopyridines C 5 H 4 (Hal)N (Hal = Cl, Br) as guest solvents for the synthesis of new salts of the family.…”
Section: Introductionmentioning
confidence: 98%